Dialogue with Civil Society as a New Quality of Socio-Economic Processes Management - Yury VASYUTIN1; Olga RUDAKOVA2; Nadezhda STEBLETSOVA2; Alexandr ESIPOV3 (Communications of International Proceedings, 2020)
The relevance of the research is determined by the Address of the President of the Russian Federation Vladimir Putin to the Federal Assembly in 2020, which forms profound and large-scale strategic changes in the constitutional, state and public construction for many years. The aim of the research is to provide an analysis of further improvement of the reformation and democratization of Russian society, which involves increasing the importance of civil society in a qualitatively new state and municipal management of socio-economic processes in the country, including processes in the socio-cultural sphere. The authors focus on the difficult conditions of the international situation, the consequences of coronavirus pandemic, with regard to which state and public institutions need to solve large-scale problems of socio-economic development without delay. It requires a new quality of state governance in accordance with direct dialogue with citizens.
Keywords: Address of the President of the Russian Federation; constitutional reforms; state governance; civil society; public oversight; socio-cultural sphere of society.